Predicting the dynamic behavior of classical columns using two-dimensional models - K. Baros, Dimitrios; Papalou, Angeliki (International Journal of Engineering and Technology, 2018)
Ancient temples consisting of classical columns have been exposed through the years to dynamic loads with sometimes detrimental effects. Predicting their dynamic behavior is important for their restoration and preservation. This paper analyzes the behavior of classical columns under dynamic loading using simplified two-dimensional finite element models. The adequacy of these models for the prediction of the dynamic behavior of classical columns is verified comparing the numerical results with experimental measurements. The most important parameters that influence the modelâ€™s behavior are identified. The behavior of classical columns can be predicted in the direction of excitation with reasonable accuracy using two-dimensional finite element models when the properties of the models are selected appropriately.Â Â
Keywords: Monuments; Classical Column; Multi-Drum Column; Finite Elements; Dynamic Loads.